2018
DOI: 10.31557/apjcp.2018.19.11.3211
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter Concisus and Its Effect on the Expression of CDX1 and COX2

Abstract: Background:Barrett’s oesophagus (BO) is a pre-malignant condition in which normal squamous epithelium of the lower oesophagus and gastresophageal junction is replaced by columnar cells and progress to oesophageal adenocarcinoma. The increase burden of oesophagus cancer morbidity and mortality worldwide make study of factors involved in the pathogenesis of BO essential. However, most of studies that examine the environmental risk factors associated with increased incidence and prevalence of BO have largely igno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…An in vitro study indicated the relationship between esophageal colonization by C. concisus and the epithelial production of TNFα and IL-18, known to induce both an innate and adaptive immune response and to increase CDX1 and COX-2 expression. In turn, this escalates the rate of colonization and chronic inflammation, which has been shown to lead to disease progression in GERD, Barrett’s esophagus and EC [ 33 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study indicated the relationship between esophageal colonization by C. concisus and the epithelial production of TNFα and IL-18, known to induce both an innate and adaptive immune response and to increase CDX1 and COX-2 expression. In turn, this escalates the rate of colonization and chronic inflammation, which has been shown to lead to disease progression in GERD, Barrett’s esophagus and EC [ 33 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study indicated the relationship between esophageal colonization by C. concisus and the epithelial production of TNFα and IL-18, known to induce both an innate and adaptive immune response and to increase CDX1 and COX-2 expression. In turn, this escalates the rate of colonization and chronic in ammation, which has been shown to lead to disease progression in GERD, Barrett's esophagus and EC [43,44].…”
Section: Discussionmentioning
confidence: 99%